Beda Efektivitas Elektroakupunktur Dengan Tens Terhadap Nyeri Dan Fleksibilitas Lumbal Pada Pasien Nyeri Punggung Bawah Myogenik - Saifudin Zuhri; Marti Rustanti (Poltekkes Kemenkes Surakarta, 2017)
Abstrack : Lower Back Pain, Electroacupuncture, TENS, Pain, Lumbar Flexibility. Myogenic lower back pain (LBP) is a prevalence that many experienced individuals who perform daily activities. Physiotherapy technology for myogenic LBP in the form of TENS is given more clinically than electroacupuncture that has not been effectively socialized. Objective: To compare the effectiveness of TENS with electroacupuncture for pain and lumbar flexibility of myogenic LBP patients. Quasi experimental research with two groups pre and post test design. The subjects of the study were myogenic LBP patients who met the study criteria. Inclusion criteria include: (1) age 50 - 70 years, (2)willing to be the subject of research. Exclusion criteria: (1) suffer myogenic LBP followed by other disorders, (2) pacemaker use, (3) impaired sensibility, (4) malignancy in the lower back. Criteria for drop out: (1) not following therapy program more than 3 times, (2) experiencing worsening condition, (3) not present during final evaluation of research. Data were collected directly at the start of the study (pre test), pain was measured by VAS and flexibility was measured by schober test. Data were analyzed with SPSS 11.5 for windows. The results of pre-post test different test in group I with Wilcoxon test, obtained p value = 0.005 (p <0.05). Test of pre-post test in group II with Wilcoxon test, got p value = 0,004 (p <0.05). Test of difference of post test in group I and group II using Mann-Whitney test, got value p = 0,017 (p˂ 0.05). The result of change of mean difference of VAS value of pre and post therapy in group I was 45 mm while in group II was 31 mm. Conclusions: (1) there was an effect of electroacupuncture therapy on the decrease of pain in myogenic LBP patients before administered by William Flexion Exercise (p = 0,005); (2) there was effect of TENS therapy on pain reduction in myogenic LBP patients before given William Flexion Exercise (p = 0.004), (3) there was a difference in effect between electro-acupuncture therapy and TENS therapy on pain reduction in patients with myogenic LBP prior to William Flexion Exercise (p = 0.017), (4) electroacupuncture was more effective than TENS for pain reduction in patients Myogenic LBP before administered by William Flexion Exercise was compared with the mean difference between pre and post I groupVAS values greater than group II (group I = 45 mm, group II = 31 mm).